How societies remember - Connerton, Paul (Themes in the social sciences., 1989)
In treating memory as a cultural rather than an individual faculty, this book provides an account of how practices of a non-inscribed kind are transmitted in, and as, traditions. Most studies of memory as a cultural faculty focus on inscribed transmissions of memories. Connerton, on the other hand, concentrates on incorporated practices, and so questions the currently dominant idea that literary texts may be taken as a metaphor for social practices generally. The author argues that images of the past and recollected knowledge of the past are conveyed and sustained by ritual performances and that performative memory is bodily. Bodily social memory is an essential aspect of social memory, but it is an aspect which has up till now been badly neglected. An innovative study, this work should be of interest to researchers into social, political and anthropological thought as well as to graduate and undergraduate student. -- from back cover.